Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3174/ajnr.a2519
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Carotid Calcium Volume with Carotid Artery Stenosis in Symptomatic Patients

Abstract: BACKGROUND AND PURPOSE:Recent research showed a strong correlation of calcium volume scores with degree of stenosis, suggesting that calcium volume could be used in the diagnosis of carotid artery stenosis. We investigated the accuracy of the use of calcium volume scores to diagnose carotid artery stenosis in our target population of recently symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
(24 reference statements)
0
10
1
1
Order By: Relevance
“…6 Studies have investigated the relationship between the quantity of carotid calcification and the degree of luminal reduction, as determined by CT examination, reporting correlations ranging from r ¼ 0.04 to r ¼ 0.65. [7][8][9][10] Correlations are slightly stronger if the total calcification amount, including both the left and right sides of the neck, is correlated to a unilateral stenosis. 7,8,10 Panoramic radiography has also shown variable quantities of calcification in carotid plaques.…”
mentioning
confidence: 94%
“…6 Studies have investigated the relationship between the quantity of carotid calcification and the degree of luminal reduction, as determined by CT examination, reporting correlations ranging from r ¼ 0.04 to r ¼ 0.65. [7][8][9][10] Correlations are slightly stronger if the total calcification amount, including both the left and right sides of the neck, is correlated to a unilateral stenosis. 7,8,10 Panoramic radiography has also shown variable quantities of calcification in carotid plaques.…”
mentioning
confidence: 94%
“…A previous study found no correlation between calcification and the degree of stenosis on the symptomatic side and a weak correlation on the asymptomatic side, 39 and the results of a recent systematic review found that symptomatic plaques have a lower degree of calcification than asymptomatic plaques. 40 For this reason, we chose to use the highest reported stenosis in examining the correlation with carotid calcification.…”
Section: Obtaining Ultrasound Measurementsmentioning
confidence: 95%
“…13,22,23 Furthermore, extracranial carotid artery calcifications are associated with carotid artery stenosis in asymptomatic patients, but in symptomatic patients this association is less clear. [24][25][26] Moreover, calcifications can be assessed easily and quantified at MDCTA, an imaging modality increasingly used in daily clinical work-up of patients with stroke, making them a suitable and robust marker of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%